A Demographic Study on Cases of Drowning with Special Reference to Histopathological Changes of Lung and Other Tissues in a Tertiary Centre (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction:Drowning is the 3rd leading cause of unintentional injury deaths.As drowning is a preventablecause of mortality, our aims for the benefit of society at large is to minimize the events as far as possible.Objective:A clear knowledge about factors which play a major role behind such incidences is important.Ithas equal forensic importance as determination of cause and manner of death require thorough investigation.Methodology: We conducted one-year study of demographic variables and the histopathological changesin relation to lung and splenic tissues in cases of drowning deaths, in the hot and humid climatic region ofEastern India.Results: The demographic findings were presented in graphs and charts. However, none ofthe commonly known autopsy findings (histopathological) are found to be individually confirmatory ofdrowning. Conclusion:Several factors inclusive of autopsy findings, biochemical examination, radiologicaland molecular technique,are needed to be taken together as complementary methods to conclude drowningas the cause of death when bodies are recovered from water.